Determinants of the Probability of Investing in Costa Rica: An Econometric Approach Based on the Financial Literacy Survey - Vázquez Barrantes, Nayeli (2025)
This article addresses the identification of the factors that determine whether an adult over 18 years of age is an investor in financial instruments beyond traditional savings, that is, participating in options other than term deposit certificates in banks or authorized financial institutions. The analysis is based on data from the Costa Rican Financial Culture Survey, published by CINPE in April 2024, and is developed using a binary logistic regression model that estimates the probability of investing based on various sociodemographic, financial, and geographic variables. The results identify a set of economic, social, and territorial factors that significantly influence this decision, and recommendations are offered aimed at strengthening financial education and deepening the development of the local financial market.